2020
DOI: 10.1017/jfm.2020.769
|View full text |Cite
|
Sign up to set email alerts
|

Dipoles and streams in two-dimensional turbulence

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 69 publications
6
20
0
Order By: Relevance
“…The results in [4] extended the previous models in some interesting directions, especially regarding the decay of unforced turbulence in the early period in which the spectral scale of the energy has not grown enough to be affected by the simulation domain. It was found that the largest structures of the kinetic energy take the form of elongated high-speed jets, flanked by a subset of large vortices that move relatively slowly with respect to the global root-mean square (r.m.s.)…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…The results in [4] extended the previous models in some interesting directions, especially regarding the decay of unforced turbulence in the early period in which the spectral scale of the energy has not grown enough to be affected by the simulation domain. It was found that the largest structures of the kinetic energy take the form of elongated high-speed jets, flanked by a subset of large vortices that move relatively slowly with respect to the global root-mean square (r.m.s.)…”
Section: Introductionsupporting
confidence: 68%
“…Case N L init /L q 0 L/ν N t λ ω0 /L λ q0 /L ω 0 t F ω F /ω 0 q F /q 0 Symbol T512 The next-to-last two columns in this table were wrong in [4]. The present ones are believed to be correct.…”
Section: Numerical Experimentsmentioning
confidence: 76%
See 3 more Smart Citations